2020
DOI: 10.1002/jcph.1644
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Lung Injury Related to COVID‐19 Infection: A Review and the Possible Role for Escin

Abstract: Acute lung injury (ALI) represents the most severe form of the viral infection sustained by coronavirus disease 2019 (COVID‐19). Today, it is a pandemic infection, and even if several compounds are used as curative or supportive treatment, there is not a definitive treatment. In particular, antiviral treatment used for the treatment of several viral infections (eg, hepatitis C, HIV, Ebola, severe acute respiratory syndrome–coronavirus) are today used with a mild or moderate effect on the lung injury. In fact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 75 publications
0
91
0
3
Order By: Relevance
“…A Belgium study CT study of 216 confirmed COVID-19 patients, which involved the scoring of lung damage found that there were no differences between age or time from onset of the disease, but that men had more extensive lung damage (9.2 ± 5 versus 7.0 ± 4.8, p = 0.001) with a trend toward more bilateral lung involvement (89.3% versus 78.8%, p = 0.06) [72]. Even for those who do not go on to develop ARDS or ALI, there can be residual pathology, including alveolar damage and fibrosis that will compromise lung function in the longer term [73,74,75].…”
Section: Longer Term Health Implications For Menmentioning
confidence: 99%
“…A Belgium study CT study of 216 confirmed COVID-19 patients, which involved the scoring of lung damage found that there were no differences between age or time from onset of the disease, but that men had more extensive lung damage (9.2 ± 5 versus 7.0 ± 4.8, p = 0.001) with a trend toward more bilateral lung involvement (89.3% versus 78.8%, p = 0.06) [72]. Even for those who do not go on to develop ARDS or ALI, there can be residual pathology, including alveolar damage and fibrosis that will compromise lung function in the longer term [73,74,75].…”
Section: Longer Term Health Implications For Menmentioning
confidence: 99%
“…Due to the high similarity, many approved or pre-clinical anti-SARS drugs are being tested for antiviral activity against SARS-CoV-2. For example, escin ( Gallelli, 2020 ) and sodium aescinate injection (trial filed in China with ID : ChiCTR2000029742) have been registered. As natural products has been historically used for respiratory infection, there is arising voice calling for the repurposing of natural products for COVID-19 ( Wang D. et al., 2020 ).…”
Section: Natural Products Inhibiting Human Coronavirusmentioning
confidence: 99%
“…[23][24][25] For example, excessive inflammation has been associated with severe respiratory effects and detrimental symptoms. 26,27 Awareness of this issue has led to the use of antiinflammatory agents, such as dexamethasone, to significantly reduce mortality in COVID-19 patients. 28 Emerging evidence indicates that SARS-CoV-2 may also induce autoantibodies.…”
Section: Introductionmentioning
confidence: 99%